Self-assembly of ultrathin Cu2MoS4 nanobelts for highly efficient visible light-driven degradation of methyl orange. Issue 43 (15th September 2015) - Zhang, Ke; Chen, Wenxing; Lin, Yunxiang; Chen, Haiping; Haleem, Yasir A.; Wu, Chuanqiang; Ye, Fei; Wang, Tianxing; Song, Li
Abstract : We demonstrate ultrathin self-assembled Cu2 MoS4 nanobelts synthesized by using Cu2 O as the starting sacrificial template via a hydrothermal method. Abstract : We demonstrate ultrathin self-assembled Cu2 MoS4 nanobelts synthesized by using Cu2 O as the starting sacrificial template via a hydrothermal method. The nanobelts exhibit strong light absorption over a broad wavelength spectrum, suggesting their potential application as photocatalysts. The photocatalytic activity of nanobelts is evaluated by the degradation of Methyl Orange (MO) dye under visible light irradiation. Notably, the nanobelts can completely degrade 100 mL of 15 mg mL −1 MO in 20 minutes with excellent recycling and structural stability, suggesting their excellent photocatalytic performance. In comparison with a sheet-like sample, the high efficiency of the self-assembled Cu2 MoS4 nanobelts is attributed to a high surface area and a unique band gap, agreeing with the nitrogen adsorption analysis and photoluminescence spectra. This study offers a self-assembled synthetic route to create new multifunctional nanoarchitectures composed of atomic layers, and thus may open a window for greatly extending potential applications in water pollution treatment, photocatalytic water-splitting, solar cells and other related fields.